Information retrieval technology : 14th Asia Information Retrieval Societies Conference, AIRS 2018, Taipei, Taiwan, November 28-30, 2018, Proceedings /: 14th Asia Information Retrieval Societies Conference, AIRS 2018, Taipei, Taiwan, November 28-30, 2018, Proceedings. (2018) - Unknown
No abstract available